2006
DOI: 10.1093/ndt/gfl469
|View full text |Cite
|
Sign up to set email alerts
|

Urinary tumour necrosis factor-  excretion independently correlates with clinical markers of glomerular and tubulointerstitial injury in type 2 diabetic patients

Abstract: In patients with type 2 diabetes, urinary TNFalpha excretion is elevated and correlates with severity of renal disease in terms of both glomerular and tubulointerstitial damage, suggesting a significant role for TNFalpha in the pathogenesis and progression of renal injury in diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
101
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(110 citation statements)
references
References 28 publications
8
101
1
Order By: Relevance
“…In the present study, the results showed that the pro-inflammatory cytokines TNF-α, IL-1β and IL-6 were notably decreased in SIRT4-overexpressing podocytes with glucose stimulation. TNF-α plays an important role in the development and progression of diabetic nephropathy supported by the observation of increases in renal TNF-α levels in diabetic animal models and patients (37,38), indicating that increased TNF-α levels result in renal damage. Clinical studies have reported significant increases in the renal production of IL-1β and IL-6 in patients with type 2 diabetic nephropathy compared with that in diabetic patients without nephropathy, suggesting a role of IL-1β and IL-6 in the pathogenesis of diabetic nephropathy (39,40).…”
mentioning
confidence: 97%
“…In the present study, the results showed that the pro-inflammatory cytokines TNF-α, IL-1β and IL-6 were notably decreased in SIRT4-overexpressing podocytes with glucose stimulation. TNF-α plays an important role in the development and progression of diabetic nephropathy supported by the observation of increases in renal TNF-α levels in diabetic animal models and patients (37,38), indicating that increased TNF-α levels result in renal damage. Clinical studies have reported significant increases in the renal production of IL-1β and IL-6 in patients with type 2 diabetic nephropathy compared with that in diabetic patients without nephropathy, suggesting a role of IL-1β and IL-6 in the pathogenesis of diabetic nephropathy (39,40).…”
mentioning
confidence: 97%
“…These studies suggest a direct and independent association between the levels of this cytokine and clinical markers of glomerular and tubulointerstitial damage, with a significant rise in serum and urinary TNF-␣ as diabetic nephropathy progresses. 69,92,93 …”
Section: Tnf-␣mentioning
confidence: 99%
“…7,16,19 -21,30 -32 Among these, the evidence for TNF-␣ as a pathogenic factor in the very early stages of DN in the experimental models of type 1 diabetes suggests that it has potential as a marker of kidney injury, as reviewed recently by Navarro et al 32 These authors also provided clinical data showing that urinary TNF-␣ was significantly and independently associated with both glomerular and tubulointerstitial lesions in type 2 diabetes 33 ; however, in our study, urinary TNF-␣ was not detectable in the majority of patients.…”
Section: Cd44mentioning
confidence: 99%